PENGARUH MANAJEMEN KONFLIK DAN MANAJEMEN RISIKO TERHADAP EFEKTIVITAS TENAGA KERJA PADA PT “X” - Joonner Rambe (Fakultas Ekonomi Universitas Borobudur, 2018)
In this study, the influence of conflict management and risk management on work effectiveness in company activities in anticipating risk management in the daily operations of the company is summarized in a number of specific categories. The focus is on increasing employee productivity through improving work effectiveness. In this study used a multiple regression analysis method, in order to get perceptions going forward. The results obtained from multiple regression equations are Y = 20.781 + 0.659 X1 + 0.085 X2, Correlation (R) is 0.828, R Square is 0.686 while the coefficient of determination (Adjusted R Square) from the output of regression statistics in this study is 0.674 , this explains that the contribution given to conflict management variables, and risk management to the effectiveness of the workforce is 67.4% while the remaining 32.6% is influenced by other factors not examined in this study such as organizational climate, commitment, compensation, and others. Key words: conflict management, risk management, work effectiveness